Evaluating Service Quality from A Physical Perspective in Missionary Hospitals in Ernakulum District - Joseph, Rajesh; Kumar, B. Selvaveera (Journal of Neonatal Surgery, 2025)
This study assesses the missionary hospitals in the Ernakulum District's service quality from a physical perspective standpoint. This research combines physical perspective health indicators with healthcare service management by looking at how various aspects of service quality—like responsiveness, empathy, and reliability—affect patient health outcomes. The goal of the study is to determine how hospital service quality affects patients' overall recovery and well-being by analysing physical perspective markers of health, health records, and patient feedback. The results are intended to shed light on the ways that better physical perspective health outcomes can be achieved through improving service quality in healthcare settings, which can then improve public health in the area. This multidisciplinary approach emphasizes the critical connection between patients' physical perspective health and high-quality healthcare services.